Tricuspid aortic stenosis with systolic dysfunction in a 14-year-old boy: Critical stenosis, noncompaction or secondary fibroelastosis?. Issue 3 (2015) - Sinha, Santosh Kumar; Thakur, Ramesh; Varma, Chandra Mohan; Goel, Amit; Kumar, Ashutosh; Jha, Mukesh Jitendra; Mishra, Vikas
No abstract available